Treatment of a residual cyst located in the upper maxilla: a case report - Andrés Antonio Romero-Blanquicett; Adel Martínez-Martínez; Antonio José Díaz-Caballero (Universidad de Antioquia, 2018)
Odontogenic cysts are usually intraosseous and are classified into developmental and inflammatory. Residual cysts are inflammatory in nature and result from the extraction of a tooth with a radicular cyst, but with no removal of the lesion remnants in the same surgical procedure. They are mainly located in the maxilla, show a slight predilection for males, and are usually asymptomatic. This article reports the case of a 64-year-old man who consulted for an increase in bulk in the anterior edentulous area of the maxilla several years after the extraction of dental organs 11 and 12. The treatment consisted of buccal wall osteotomy, enucleation and curettage of the residual cyst, using a Newman flap from teeth 13 to 23. Postoperative controls were periodically performed, showing adequate healing.